2011
DOI: 10.5152/tpd.2011.12
|View full text |Cite
|
Sign up to set email alerts
|

A Nasopharyngeal Human Infestation Caused by Linguatula serrata Nymphs in Van Province: A Case Report

Abstract: The reason for the presentation of this case is that Linguatula serrata, a parasite rarely encountered in humans, was found in a patient in Van province. The patient, who was 26 years old, lived in Erciş a town in Van province, East Turkey. She was admitted to the Outpatient Clinic of Infectious Diseases of Erciş Government Hospital with a complaint of coughing a few worms about 4 cm long from the oral cavity, and also sore throat, partial voice loss and vomiting. The polyclinic doctor suspected that the worm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Human infection is as the result of ingestion of third stage larvae of L.serrata found in raw liver or lymph nodes of sheep, goats, cattle and camels. Ingestion of L. serrata nymphs can cause halzoun or marrara syndrome that is often characterized by inflammation of the upper respiratory tract, swelling of the submaxillary and cervical lymph nodes and occasionally abscess formation in the eyes or ears [31][32][33][34][35][36][37][38]9] , Sporadic incidence of halzoun in humans has also been reported in Iran [7] . The high prevalence of infection observed in ruminants is of concern owing to the zoonotic nature of the parasite and the risk of infection to humans and other animals.…”
Section: Discussionmentioning
confidence: 99%
“…Human infection is as the result of ingestion of third stage larvae of L.serrata found in raw liver or lymph nodes of sheep, goats, cattle and camels. Ingestion of L. serrata nymphs can cause halzoun or marrara syndrome that is often characterized by inflammation of the upper respiratory tract, swelling of the submaxillary and cervical lymph nodes and occasionally abscess formation in the eyes or ears [31][32][33][34][35][36][37][38]9] , Sporadic incidence of halzoun in humans has also been reported in Iran [7] . The high prevalence of infection observed in ruminants is of concern owing to the zoonotic nature of the parasite and the risk of infection to humans and other animals.…”
Section: Discussionmentioning
confidence: 99%
“…serrata has also been reported. Yilmaz et al reported a 26 year old woman in Van Province complaining of coughing Yilmaz et al (2011) . Also, a pentastomiasis case in a 70 year old native farmer from Keningau, Sabah, East Malaysia was reported in 2011 with a one-month history of upper abdominal discomfort, weight loss, anorexia, jaundice, and dark urine.…”
Section: Discussionmentioning
confidence: 99%
“…A 28-year-old woman affected with linguatulosis and with respiratory symptoms, including sneezing and nasal discharge, representing the clinical signs of Marrara was described in Iran (Maleky, 2001). Human nasopharyngel linguatulosis was also reported from the Van Province of Turkey close to the North Western region of Iran (Yilmaz et al, 2011). Several other studies have assessed the prevalence of L. serrata in dogs (Khalil, 1970;Akyol et al, 1995;Oryan et al, 1997;Meshgi and Asgarian, 2003;Aldemir, 2004;Oryan et al, 2008), one-humped camels (Mobedi et al, 1988;Oryan et al, 1993;Tajik et al, 2007;Haddadzadeh et al, 2010;Radfar et al, 2010), two-humped camels (Haddadzadeh et al, 2009), buffaloes (Sisakumar et al, 2005;Tajik et al, 2008;Jalali, 2010), sheep (Esmail-Nia et al, 2000;Shekarforoush et al, 2004;Tavassoli et al, 2007a;Ravindran et al, 2008;Gul et al, 2009;Fard et al, 2011), cattle (Tajik et al, 2006;Hami et al, 2009;Fard et al, 2010b;Youssef and Hadizedeh-Moalem, 2010), goats (Saiyari et al, 1996;Razavi et al, 2004;Tavassoli et al, 2007b;Mir et al, 2009;Fard et al, 2010a;) and small ruminants (Vatsya et al, 2011).…”
mentioning
confidence: 87%